Resonance assignment of As-p18, a fatty acid binding protein secreted by developing larvae of the parasitic nematode Ascaris suum - Ibáñez Shimabukuro, Marina (2014)
As-p18 is produced and secreted by larvae of the parasitic nematode Ascaris suum as they develop within their eggs. The protein is a member of the fatty acid binding protein (FABP) family found in a wide range of eukaryotes, but is distinctive in that it is secreted from the synthesizing cell and has predicted additional structural features not previously seen in other FABPs. As-p18 and similar proteins found only in nematodes have therefore been designated 'nemFABPs'. Sequence-specific 1H, 13C and 15N resonance assignments were established for the 155 amino acid recombinant protein (18.3 kDa) in complex with oleic acid, using a series of three-dimensional triple-resonance heteronuclear NMR experiments. The secondary structure of As-p18 is predicted to be very similar to other FABPs, but the protein has extended loops that have not been observed in other FABPs whose structures have so far been solved.